D5.8 Dissemination, Exploitation, and Communication Strategy report - 1 - Debano, Isabelle; Dvořáková, Martina; Fiorini, Susanna; Mystakopoulos, Fotis; Riera, Clara (Zenodo (CERN European Organization for Nuclear Research), 2026)
This document outlines the results regarding Dissemination, Exploitation, and Communication activities of the ALMASI project for the last 18 months, from 1st January 2025 to 30 June 2026. Work Package 5 (WP5) is responsible for delivering communication, engagement, dissemination, and exploitation actions, although the results reflect the contributions of all consortium partners in many aspects of this work. The project navigates unique challenges, including the multilingual nature of its communication—spanning four languages—to ensure inclusivity and accessibility across its diverse audience. To address the diversity of its audience, the project has taken into account various ways of communicating, adapting to different channels, usage patterns, and cultural contexts. This includes a thorough analysis of key messages tailored to specific stakeholders, as well as strategic planning to engage with each group effectively. By doing so, ALMASI ensures that its Key Exploitable Results are not only developed but also exploited in a way that resonates with and empowers its global community.Despite these first challenges, ALMASI succeeds in creating a common ground and shared path for its stakeholders, fostering alignment and cohesion in its mission.